Socioeconomic differences in takeaway food consumption and their contribution to inequalities in dietary intakes. Issue 10 (14th July 2009) - Miura, K; Giskes, K; Turrell, G
Abstract : Background: Takeaway consumption has been increasing and may contribute to socioeconomic inequalities in overweight/obesity and chronic disease. This study examined socioeconomic differences in takeaway consumption patterns and their contributions to dietary intake inequalities. Method: Cross-sectional dietary intake data from adults aged between 25 and 64 years from the Australian National Nutrition Survey (n = 7319, 61% response rate). Twenty-four-hour dietary recalls ascertained intakes of takeaway food, nutrients and fruit and vegetables. Education was used as a socioeconomic indicator. Data were analysed using logistic regression and general linear models. Results: Thirty-two per cent (n = 2327) consumed takeaway foods in the 24-hour period. Lower educated participants were less likely than their higher educated counterparts to have consumed total takeaway foods (OR 0.64; 95% CI 0.52 to 0.80). Of those consuming takeaway foods, the lowest educated group was more likely to have consumed "less healthy" takeaway choices (OR 2.55; 95% CI 1.73 to 3.77), and less likely to have consumed "healthy" choices (OR 0.52; 95% CI 0.36 to 0.75). Takeaway foods made a greater contribution to energy, total fat, saturated fat and fibre intakes among lower than among higher educated groups. Lower likelihood of fruit and vegetable intakes were observed among "less healthy" takeaway consumers, whereas a greater likelihood of their consumption was found among "healthy" takeaway consumers. Conclusions: Total and the types of takeaway foods consumed may contribute to socioeconomic inequalities in intakes of energy, total and saturated fats. However, takeaway consumption is unlikely to be a factor contributing to the lower fruit and vegetable intakes among socioeconomically disadvantaged groups.